Clinical and Microbiological Effects of Photodynamic Therapy Associated with Non-surgical Treatment in Aggressive Periodontitis - Mohammad Taghi Chitsazi; Adileh Shirmohammadi; Reza Pourabbas; Nader Abolfazli; Ilnaz Farhoudi; Behrouz Daghigh Azar; Farrokh Farhadi (Tabriz University of Medical Sciences, 2014)
Background and aims. The aim of this study was to compare the effectiveness of adjunctive photodynamic therapy (PDT) in the treatment of aggressive periodontitis. Materials and methods. A total of 24 patients with clinical diagnosis of aggressive periodontitis received scaling and root planing (SRP) for periodontal treatment. In a split-mouth design study, the teeth of one quadrant of each arch with ≥4 mm of probing depth were selected randomly for additional treatment with PDT (test group). PDT was performed with a diode laser beam with a wavelength of 670-690 nm and a power of 75 Mw. The control group consisted of selected teeth of the contralateral quadrant (SRP only). Before any treatment, subgingival plaque samples were collected by an endodontic paper cone for microbiological analysis by real-time polymerase chain reaction (PCR) for detection of Aggregatibacter actinomy-cetecommitans. Clinical parameters including clinical attachment loss (CAL) as primary outcome, plaque index (PI), bleed-ing on probing (BOP), probing depth (PD) and gingival recession (REC) were measured at baseline and after 90 days. Inter-group and intra-group statistical analyses were performed. Results. Treatment groups showed an improvement in all the clinical parameters and a significant reduction in the counts of A. actinomycetecommitans at 90 days compared to baseline (P < 0.05). None of the periodontal parameters exhibited sig-nificant differences between the two groups (P > 0.05). Conclusion. Within the limitations of this study, the results did not show additional benefits from PDT as an adjunctive treatment for patients with aggressive periodontitis.